2006
DOI: 10.1519/r-17955.1
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Plyometric vs. Dynamic Stabilization and Balance Training on Power, Balance, and Landing Force in Female Athletes

Abstract: Neuromuscular training protocols that include both plyometrics and dynamic balance exercises can significantly improve biomechanics and neuromuscular performance and reduce anterior cruciate ligament injury risk in female athletes. The purpose of this study was to compare the effects of plyometrics (PLYO) versus dynamic stabilization and balance training (BAL) on power, balance, strength, and landing force in female athletes. Either PLYO or BAL were included as a component of a dynamic neuromuscular training r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
264
4
14

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 230 publications
(293 citation statements)
references
References 23 publications
11
264
4
14
Order By: Relevance
“…7,8 Based on this notion, numerous investigations and ACL injury-prevention programs have been implemented in an effort to reduce landing forces. [9][10][11] After initial ground contact during landing, the quadriceps act eccentrically to counter the knee flexion imposed by ground reaction forces. Research in the cadaveric knee 12,13 and in vivo 14 has indicated that quadriceps activation introduces stress and strain to the ACL and is capable of producing ACL injury and rupture in vitro.…”
mentioning
confidence: 99%
“…7,8 Based on this notion, numerous investigations and ACL injury-prevention programs have been implemented in an effort to reduce landing forces. [9][10][11] After initial ground contact during landing, the quadriceps act eccentrically to counter the knee flexion imposed by ground reaction forces. Research in the cadaveric knee 12,13 and in vivo 14 has indicated that quadriceps activation introduces stress and strain to the ACL and is capable of producing ACL injury and rupture in vitro.…”
mentioning
confidence: 99%
“…Dynamic stabilization is ability to maintain equilibrium during the transition from motion to a stationary position, such as a landing movement (Myer, Ford, Brent, & Hewett, 2006). Dynamic balance is the capacity to maintain the center of mass over a fi xed base of support under a movement challenge.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, for every 1.3-mm increase in side-to-side difference in AP knee displacement (measured by KT-2000, MEDmetric, San Diego, CA, USA) the odds of ACL injury increased fourfold and positive knee hyperextension increased ACL injury odds fivefold [76]. Females who experienced subsequent ACL injury had decreased hamstrings strength but similar quadriceps strength compared with male control subjects [63].…”
Section: Prediction and Assessment Of At Risk Individualsmentioning
confidence: 99%